Research Methods for Social Justice and Equity in Education - Strunk, Kamden K.; Locke, Leslie Ann (Springer, 2019)
Typical instruction in research methods in education can be detached from real issues and real problems in education; it often focuses on the nuts and bolts of research processes, and sometimes with examples that are less than substantive. Similarly, students often progress through their research methods coursework with no real sense of how those methods can contribute to moves toward (or away from) equity. Our goal with this book is to provide theoretical, methodological, and practical information on how to mobilize educational research and research methods for social justice and equity in education.